2022
DOI: 10.3389/fmars.2022.916025
|View full text |Cite
|
Sign up to set email alerts
|

Basin-Scale Underway Quantitative Survey of Surface Microplankton Using Affordable Collection and Imaging Tools Deployed From Tara

Abstract: World ocean plankton quantitative biodiversity data are still severely limited due to the high cost and logistical constraints associated to oceanographic vessels and collection/analytic devices. Here, we report the first use of an affordable and open-source plankton collection and imaging kit designed for citizen biological oceanography, composed of a high-speed surface plankton net, the Coryphaena, together with a portable in-flux automated imaging device, the PlanktoScope. We deployed this kit in December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The PlanktoKit 1.0, which costs less than $3,000 in parts, consists of a cruising-speed plankton collection system (von Ammon et al, 2020), a PlanktoScope (Pollina et al, 2022), a new cost-effective plankton DNA collection-kit we call the 'Lamprey', and a tablet computer to drive the PlanktoScope, record all contextual and meta-data, and visualize and record plankton images and movies. We have shown that these frugal tools deployed from sailing boats can generate consistent, planetary scale genetic (this paper) and morphological (Meŕiguet et al, 2022) data, paving the way for the Plankton Planet vision (Box 1). Deployment of the first kits on key navigation loops and routes will start in 2023 in the Atlantic oceans as part of the European research program AtlantEco.…”
Section: Toward Seatizen Field-aquascopes For Perennial Cooperative M...mentioning
confidence: 82%
See 2 more Smart Citations
“…The PlanktoKit 1.0, which costs less than $3,000 in parts, consists of a cruising-speed plankton collection system (von Ammon et al, 2020), a PlanktoScope (Pollina et al, 2022), a new cost-effective plankton DNA collection-kit we call the 'Lamprey', and a tablet computer to drive the PlanktoScope, record all contextual and meta-data, and visualize and record plankton images and movies. We have shown that these frugal tools deployed from sailing boats can generate consistent, planetary scale genetic (this paper) and morphological (Meŕiguet et al, 2022) data, paving the way for the Plankton Planet vision (Box 1). Deployment of the first kits on key navigation loops and routes will start in 2023 in the Atlantic oceans as part of the European research program AtlantEco.…”
Section: Toward Seatizen Field-aquascopes For Perennial Cooperative M...mentioning
confidence: 82%
“…This requests uncomfortable sailing operations impacting the cruising speed, and it was identified as the primary limiting factor for denser sampling. We have therefore been working on the design of new miniaturized high-speed nets (von Ammon et al, 2020;Meŕiguet et al, 2022), inspired by our successful experience during the Tara Pacific expedition (Gorsky et al, 2019), as well as simple manual pumping system allowing aspiration of seawater at cruising speed, followed by filtration through a small net system installed on board. The latter device has the advantage of being able to collect pristine water that can also be used to extract DNA/RNA from the smaller plankton size fractions enriched in bacteria, archaea and viruses.…”
Section: Sampling Total Plankton At Sailing-speedmentioning
confidence: 99%
See 1 more Smart Citation